2023
DOI: 10.7759/cureus.38083
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Monkeypox: A Comparison of Other Poxviruses to the Monkeypox

Abstract: The current monkeypox (MPX) outbreak has been declared a public health emergency of international concern (PHEIC) by the World Health Organization (WHO). It is a zoonotic disease that has persisted in the African basin for decades but suddenly exploded into the international sphere this year. In this paper, we provide a comprehensive overview of monkeypox, including a hypothesis of the rapid spread of the virus, its epidemiology and clinical features, a comparison with other orthopoxviruses such as chickenpox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…One of the most likely reasons for the increasing prevalence of monkeypox was the cessation of the smallpox vaccination programs in 1980, and the resultant decrease in herd immunity against poxviruses ( 34 , 35 , 60 ). Several studies have reported monkeypox to be more common in individuals who were not vaccinated against smallpox ( 52 , 95 ). The smallpox vaccine could be as much as 85% effective in preventing monkeypox, so since the cessation of the smallpox immunization programs, immunity to similar orthpoxviruses (e.g., monkeypox) has also decreased ( 1 , 15 , 23 , 24 , 35 , 39 ).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most likely reasons for the increasing prevalence of monkeypox was the cessation of the smallpox vaccination programs in 1980, and the resultant decrease in herd immunity against poxviruses ( 34 , 35 , 60 ). Several studies have reported monkeypox to be more common in individuals who were not vaccinated against smallpox ( 52 , 95 ). The smallpox vaccine could be as much as 85% effective in preventing monkeypox, so since the cessation of the smallpox immunization programs, immunity to similar orthpoxviruses (e.g., monkeypox) has also decreased ( 1 , 15 , 23 , 24 , 35 , 39 ).…”
Section: Historymentioning
confidence: 99%
“…In addition, the histologic features of monkeypox are very similar to those of smallpox and cowpox, although they are both noticeably different from other pox viruses ( 56 , 147 ). The crop-like, less centrifugally distributed lesions (than smallpox), and especially the presence of lymphadenopathy may indicate monkeypox ( 56 ), as lymphadenopathy is not a common feature of smallpox ( 95 ). Lymphadenopathy in the submandibular and the cervical or inguinal regions are also considered to be a key diagnostic feature that distinguishes monkeypox from smallpox ( 3 , 148 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Monkeypox data from the DRC accounted for more than one-third of the eligible articles [2,4,[8][9][10][11]13,14,17,18,[20][21][22][23]. The remaining articles had monkeypox data from Gabon [5,7], Sierra Leone [3,20], Cameroon [4,6,23], CAR [4,12,15,[24][25][26][27][28], ROC [13,16,19,29], Cote d'Ivoire [3,4], Nigeria [3,30], Liberia [3,[31][32][33][34], and Pakistan [35]. Note: Two articles [3,4] described data for more than one country; therefore, the total number of articles per country exceeds 25.…”
Section: Number Of Reports By Countrymentioning
confidence: 99%
“…We identified 25 peer-reviewed articles [1][2][3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][28][29][30] Each box denotes the number of probable cases, number of confirmed cases (n), number of deaths, and/or CFR (%). Where suspect cases were tested and found positive for another disease, these were subtracted from the suspect case total.…”
Section: Number Of Cases By Countrymentioning
confidence: 99%
“…The main complications of this entity include bacterial superinfection, bronchopneumonia, encephalitis, and keratitis [ 10 ]. Higher-risk populations include neonates, children, and those with immunodeficiency [ 11 ]. Although there are limited data among people living with HIV (PLWHIV), it appears that those with persistent detectable viral load, low CD4 count, or a recent HIV-related illness are more likely to develop complications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%